2012
DOI: 10.1155/2012/108206
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and Genotype Distributions in Turkish Preeclampsia Patients

Abstract: Placental, immune and genetic factors are thought to play an important role in preeclampia (PE)'s pathophysiology. Angiotensin-Converting Enzyme (ACE) plays a vital role in the renin-angiotensin-system (RAS) which regulates blood pressure by converting angiotensin I into a powerfull vasoconstrictor angiotensin II. A deletion polymorphism (D allele) has been reported to be associated with elevated ACE activity. The aim of the this study was to investigate whether there is an association between angiotensin conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Uma et al (2010) found that the DD genotype of ACE was related to early-onset preeclampsia, although no marked changes in RAS were detected. A recent study by Bereketoglu et al (2012) also suggested a higher incidence of the DD genotype in Turkish preeclampsia patients in all the three modelscodominant, recessive, and dominant. Meanwhile, based on 30 case-control studies, a meta-analysis by Chen et al (2012) showed a strong relationship between the DD genotype of ACE and a higher risk of pregnancy hypertensive disorders, especially for Asians and Caucasians.…”
Section: Ace Polymorphism In Preeclampsiamentioning
confidence: 82%
“…Uma et al (2010) found that the DD genotype of ACE was related to early-onset preeclampsia, although no marked changes in RAS were detected. A recent study by Bereketoglu et al (2012) also suggested a higher incidence of the DD genotype in Turkish preeclampsia patients in all the three modelscodominant, recessive, and dominant. Meanwhile, based on 30 case-control studies, a meta-analysis by Chen et al (2012) showed a strong relationship between the DD genotype of ACE and a higher risk of pregnancy hypertensive disorders, especially for Asians and Caucasians.…”
Section: Ace Polymorphism In Preeclampsiamentioning
confidence: 82%
“…Inhibition/prevention of angiotensin II production has been reported to be beneficial in the prevention of type 2 diabetes as an increase in angiotensin II level contributes to insulin insensitivity in the peripheral tissues (Chu and Leung 2009). Bereketoglu et al (2012) also agreed that prevention of angiotensin II formation by the inhibition of ACE activity could be a useful therapeutic approach in the management of high blood pressure in both diabetic and non-diabetic patients.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that genetic factors such as gene polymorphisms of the RAS may play an important role in the regulation of blood pressure in PE [21,22,23]. We revealed that pregnant women carrying the TT genotype of the AGT gene are prone to early onset of severe PE, and serum VEGF, PlGF, and sFlt-1 together contribute to the pathogenesis of PE.…”
Section: Discussionmentioning
confidence: 75%